EFEKTIVITAS PROGRAM INOVASI WESELPOS CASH TO ACCOUNT DI KANTOR POS TASIKMALAYA - Mikdar Abdul; Husen Saeful Anwar; Faizal Pikri (GoAcademica Research dan Publishing, 2022)
This study describes the effectiveness of the Cash to Account Innovation program at the Tasikmalaya Post Office. From this research, it can be described how the implementation of the Cash to Account Innovation program at the Tasikmalaya Post Office has been held for a long time, from 2015 to the present. The effectiveness of the Cash to Account Innovation program at the Tasikmalaya Post Office is measured in order to determine the extent to which the effectiveness of the Cash to Account Innovation program at the Tasikmalaya Post Office reaches the goals that have been set previously, which are known from the program effectiveness indicators by Ni Wayan Budiani, namely accuracy program targets, program socialization, program objectives, and program monitoring. This study uses descriptive qualitative research methods. Data collection techniques with interviews, observations, and documentation. The in-depth interviews were conducted by researchers using a purposeful sampling technique where the researchers interviewed the post office financial manager, service manager, customer service and post office service users. The results of the study indicate that the effectiveness of the cash to account innovation program at the Tasikmalaya post office has not yet been achieved.